Native Pulmonic Valve Endocarditis due to Mycobacterium fortuitum: A Case Report and Literature Review - Aaron M. Mulhall; Renee S. Hebbeler-Clark (Case Reports in Infectious Diseases)
Endocarditis secondary to Mycobacterium fortuitum is a rare entity often involving prosthetic valves and rarely native valves. Pulmonic valve endocarditis secondary to any organism is rare. We report the first case of native pulmonic valve endocarditis secondary to M. fortuitum and a literature review of native valve M. fortuitum endocarditis.